2018
DOI: 10.1016/j.heliyon.2018.e00688
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of benzodiazepines use in primary care adults with anxiety disorders

Abstract: BackgroundBenzodiazepines are among the most commonly prescribed drugs for anxiety disorders. While they are indicated as adjunctive treatment for short-term use according to clinical practice guidelines, previous studies have shown patterns of long-term use of benzodiazepines, which is problematic due to side effects, dependence and potential of abuse. The aims of this study were to examine among a large sample of primary care adults suffering from anxiety disorders: 1) benzodiazepine use patterns; and 2) cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
0
22
0
4
Order By: Relevance
“…Most of the studies identified by the literature search involved patients with anxiety disorders who were not taking BZD. Although long‐term use of BZD has been reported in several countries, 20, 21 few studies have examined the effects of CBT for BZD discontinuation. Second, because we included different anxiety disorders, it would have been best to conduct a subgroup analysis for each anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies identified by the literature search involved patients with anxiety disorders who were not taking BZD. Although long‐term use of BZD has been reported in several countries, 20, 21 few studies have examined the effects of CBT for BZD discontinuation. Second, because we included different anxiety disorders, it would have been best to conduct a subgroup analysis for each anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, however, BZD anxiolytics are often used for the long‐term treatment of anxiety disorders 20, 21 . An observational study in a Canadian primary‐care setting found that 22.6% of patients with an anxiety disorder used BZD and that 79.6% were long‐term BZD users, over the course of 180 days 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, benzodiazepines are not recommended for long-term treatment owing to side effects and potential addiction. 53 Benzodiazepines are usually administered for severe anxiety disorders and are administered at night to overcome insomnia. 54,55 In our study, the estimated annual treatment cost for outpatients with schizophrenia from a healthcare perspective was USD 236 per patient.…”
Section: Discussionmentioning
confidence: 99%
“…No tratamento de transtorno de ansiedade estes medicamentos são adotados como uma opção adjunta aos antidepressivos, em dosagem regular e a curto prazo, com o objetivo de atenuar os sintomas do paciente, até que antidepressivos promovam o efeito desejado. A duração máxima recomendada para o tratamento com BZDs deve ser de 2 a 8 semanas, preferencialmente não excedendo 12 semanas 6 .…”
Section: O S Benzodiazepínicos (Bzds) São Drogasunclassified